Investigation into Emotional Intelligence, Social and Emotional Loneliness and Digital Game Addictions of Mid-Adolescent Students - Bahar Güler (Research in Sport Education and Sciences)
The research was conducted to examine the emotional intelligence, social and emotional loneliness and digital game addictions of secondary school students. A personal information form designed by the researchers in line with the literature, "Social and Emotional Loneliness Scale" (SELSA) developed by DiTommaso, Brannen, and Best (2004) and adapted to Turkish by Çeçen (2007), “Trait Emotional Intelligence Questionnaire – Adolescent Short Form ” (TEIQue-ASF) developed by Petrides and Furnham (2000) and adapted into Turkish by Ergin (2017) and the “Digital Game Addiction Scale” (GAS) developed by Lemmens, Valkenburg and Peter (2009) and adapted into Turkish by Irmak and Erdoğan (2015) were used to collect data. The analysis of the data was performed in computer environment with SPSS-25 statistical package programs. Skewness and kurtosis tests were performed to determine the distribution of the data. Descriptive statistics were applied to normally distributed data, t-test was used for independent groups, and simple linear Pearson correlation analysis and multiple regression test were performed to determine the relationship between scales. In conclusion, it was determined that as the digital game addiction of middle-adolescent students increased, social and emotional loneliness increased, and that emotional intelligence (5.4%) was at an explanatory level in predicting digital game addiction.